D.6 is your answer
Hope this helps!!!!
Answer:
(3,-2)
Step-by-step explanation:
The answer would be false
The equation of the parabola in the vertex form is y = (x - 3
- 5 with ( 3, -5) is the vertex of the parabola and 1 is the multiplier
In the above question, A parabolic equation is given as follows:
Y = x^2 - 6x + 4
The equation of the parabola in the vertex form is :
y = a (x - h
+ k
Where a is a multiplier in the equation and (h,k) are the coordinates of the vertex
So, in order to obtain this form, we will use the method of completing square :
Y = x^2 - 6x + 4
y =
- 6x + (9 -9) + 4
y = (x - 3
+ ( -9 + 4)
y = (x - 3
- 5
where, ( 3, -5) is the vertex of the parabola and 1 is the multiplier
Hence, The equation of the parabola in the vertex form is y = (x - 3
- 5 with ( 3, -5) is the vertex of the parabola and 1 is the multiplier
To learn more about, parabola, here
brainly.com/question/21685473
#SPJ1
Answer:
D
Step-by-step explanation:
Product means to multiply 2 numbers and for this question its 9x4. The devided by 6 part is just divided from 6. so (9x4)/6
Hope this helped!